Problematika Pertimbangan Hukum Oleh Hakim dalam Mewujudkan Keadilan di Masyarakat - Rasji; Harry Harmono (Jurnal Hukum Lex Generalis, 2024)
Legal considerations by judges play a crucial role in law enforcement and are key to realizing justice in society. From both legal and sociological perspectives, judges are often seen as representatives of noble values, even symbolically referred to as God's representatives on Earth. Therefore, each ruling is expected to reflect not only formal legal aspects but also the substantive values of justice that resonate within society. However, in reality, there is often a gap between public expectations and judicial decisions, with many judgments failing to meet society's sense of justice and truth.